2008
DOI: 10.1007/s11999-008-0432-z
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Innervation and Innervated Neurons between Hip and Inguinal Skin

Abstract: Pain originating from the hip may be referred to the groin and anterior thigh. We investigated sensory dorsal root ganglion neurons innervating the hip and the inguinal skin in rats using retrograde neurotransport and immunohistochemistry. A retrograde neurotracer FluoroGold TM was injected into the left hip or inguinal skin of rats. Seven days later, we harvested bilateral dorsal root ganglions and counted the number of Fluoro-Gold TMlabeled neurons positive for calcitonin gene-related peptide, a marker of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…Third, most dorsal root ganglia (DRG) contain both the cell bodies of sensory neurons that innervate the skeleton and skin [29; 47]. For example, the DRGs that house the sensory nerve fibers that innervate the tumor-bearing femur (lumbar ganglia) also house the cell bodies of sensory neurons that innervate the plantar surface of the skin [32; 50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, most dorsal root ganglia (DRG) contain both the cell bodies of sensory neurons that innervate the skeleton and skin [29; 47]. For example, the DRGs that house the sensory nerve fibers that innervate the tumor-bearing femur (lumbar ganglia) also house the cell bodies of sensory neurons that innervate the plantar surface of the skin [32; 50].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the number of P2X3 or TrkA expressing neurons in the DRG appears to be conserved between humans and rodents [70]. Previous studies have demonstrated that in the mouse, P2X3 receptors are expressed by sensory nerve fibers that also express Mas-related G protein-coupled receptor member D (MrgprD) + and IsolectinB 4 (IB4) + and that this population of P2X3 expressing sensory nerve fibers has been shown to densely innervate the skin but not the bone or joint [3; 14; 29; 41; 47; 69; 75]. In contrast, the great majority of sensory neurons that innervate the bone express TrkA [8; 60] (which is the cognate receptor for NGF) whereas only a minority of the sensory nerve fibers that innervate the skin express TrkA [5; 6; 27; 75].…”
Section: Discussionmentioning
confidence: 99%
“…The afferents innervating the low back or leg muscles were found in four lumbar roots including L1 (Pintér and Szolcsányi, 1995;Ohtori et al, 2003). The afferents originating from joints enter the spinal cord through, probably, the broadest range of the lumbar dorsal roots (Pintér and Szolcsányi, 1995;Ohtori et al, 2000Ohtori et al, , 2003Nakajima et al, 2008). For example, the L5/6 facet joint is innervated by five DRGs, three of which (L3-L5) innervate segmentally and two (L1-L2) nonsegmentally through the paravertebral sympathetic trunk (Ohtori et al, 2000).…”
Section: Mixed Monosynaptic and Polysynaptic Inputsmentioning
confidence: 99%
“…Birnbaum et al [8] described the hip as innervated by the obturator, femoral, sciatic, and superior gluteal nerves. Previously, we reported that dorsal root ganglion (DRG) neurons innervating the hip were distributed on multiple levels (L1-L4) [9] and that there is a difference in the level of innervation between the hip and inguinal skin [10]. Moreover, DRG neurons that innervate the hip and inguinal skin may overlap [11].…”
Section: Introductionmentioning
confidence: 99%